How do economic freedom, trade freedom, and digitization influence renewable energy consumption in G20 nations: What is the role of innovation? - Qamruzzaman, Md (International Journal of Renewable Energy Development, 2025)
This study investigates the relationship between economic freedom, trade freedom, digitalization, and innovation on renewable energy consumption among G20 nations over the period 2000–2023. Utilizing a robust empirical framework—including Dynamic Common Correlated Effects (DCCE), Instrumental Variable-adjusted DCCE (DCCE-IV), and Dynamic Seemingly Unrelated Regression (DSUR)—the analysis reveals nuanced insights into how these economic and technological dimensions shape the transition toward sustainable energy systems. Results demonstrate that a 10% rise in economic freedom correlates with a 1.112%–1.688% increase in renewable energy consumption, while trade freedom yields a positive impact ranging from 0.904% to 1.182%. Technological innovation contributes between 0.915% and 1.571%, and environmental innovation exerts an even stronger effect, ranging from 1.273% to 1.616%. Interestingly, despite the energy intensity associated with digital technologies, digitalization also supports renewable energy adoption, showing a positive influence between 1.013% and 1.526%. These findings underscore innovation's pivotal role in mediating the effects of economic policy and digital transformation on renewable energy usage. The study advocates for integrated policy approaches that simultaneously promote market liberalization, digital infrastructure, and innovation investment. This would accelerate the transition to renewable energy and help G20 nations meet Sustainable Development Goal 7 (affordable, reliable, sustainable, and modern energy for all). The results emphasize the need for synergistic strategies that connect economic openness, technological advancement, and environmental priorities, offering a roadmap for policymakers seeking to enhance clean energy deployment in large, high-impact economies.